2 Tropical Landscapes and the Ancient Maya: Diversity in Time and Space. Issue 1 (March 2014) - Chase, Arlen F.; Lucero, Lisa J.; Scarborough, Vernon L.; Chase, Diane Z.; Cobos, Rafael; Dunning, Nicholas P.; Fedick, Scott L.; Fialko, Vilma; Gunn, Joel D.; Hegmon, Michelle; Iannone, Gyles; Lentz, David L.; et al.
ABSTRACT Archaeologists have begun to understand that many of the challenges facing our technologically sophisticated, resource dependent, urban systems were also destabilizing factors in ancient complex societies. The focus of IHOPE‐Maya is to identify how humans living in the tropical Maya Lowlands in present‐day Central America responded to and impacted their environments over the past three millennia, and to relate knowledge of those processes to modern and future coupled human–environment systems. To better frame variability in ancient lowland Maya development and decline, the area that they once occupied may be subdivided into a series of geographical regions in which the collected archaeological data can be correlated with environmental differences. Although beginning as small agricultural communities occupying a variety of ecological niches in the humid tropics of Mesoamerica, the ancient Maya became an increasingly complex set of societies involved in intensive and extensive resource exploitation. Their development process was not linear, but also involved periods of rapid growth that were punctuated by contractions. Thus, the long‐term development and disintegration of Maya geopolitical institutions presents an excellent vantage from which to study resilience, vulnerability, and the consequences of decision‐making in ancient complex societies.